2023
DOI: 10.3390/educsci13070751
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Socially Significant Behaviors for Children with Autism Using Synchronous Reinforcement

Abstract: In some types of reinforcement schedules, a reinforcer is presented or given to the child and interacted with continuously while a target behavior is occurring. Previous researchers have used this type of reinforcement as an assessment tool and to study basic reinforcement processes. However, little research has explored how to effectively use these schedules to reinforce socially important responses in applied settings. The current study analyzed the implementation of synchronous reinforcement in a nonconcurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Although SSR schedules have been used to study various psychological phenomena (e.g., infant cognition and development, Siqueland & Lipsitt, 1966;Smith et al, 1963), little research has been conducted on the application of SSR for changing socially important behavior. In addition to McHugh et al (2022), a few other studies have shown SSR was effective for influencing socially important behavior including on-task behavior in preschool children (e.g., Diaz de Villegas, 2020), physical activity (Biddiss & Irwin, 2010;Faith et al, 2001), and social and motor skills in children with autism spectrum disorder (Stordahl et al, 2023). Furthermore, Diaz de Villegas et al (2020) showed SSR was preferred over a discontinuous schedule of reinforcement (i.e., an accumulated schedule in which reinforcement was yoked to the duration of on-task behavior and delivered at the end of the session) for 7 of 8 participants.…”
Section: Introductionmentioning
confidence: 99%
“…Although SSR schedules have been used to study various psychological phenomena (e.g., infant cognition and development, Siqueland & Lipsitt, 1966;Smith et al, 1963), little research has been conducted on the application of SSR for changing socially important behavior. In addition to McHugh et al (2022), a few other studies have shown SSR was effective for influencing socially important behavior including on-task behavior in preschool children (e.g., Diaz de Villegas, 2020), physical activity (Biddiss & Irwin, 2010;Faith et al, 2001), and social and motor skills in children with autism spectrum disorder (Stordahl et al, 2023). Furthermore, Diaz de Villegas et al (2020) showed SSR was preferred over a discontinuous schedule of reinforcement (i.e., an accumulated schedule in which reinforcement was yoked to the duration of on-task behavior and delivered at the end of the session) for 7 of 8 participants.…”
Section: Introductionmentioning
confidence: 99%